THE REVIEW OF DISASTER PREPAREDNESS SCHOOL PROGRAM IN INDONESIA ELEMENTARY AND HIGH SCHOOL - Kurniadi, Anwar; Bahar, Fauzi (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2020)
Schools are an essential avenue for youth to learn about disaster resilience A critical success factor for the uptake of disaster resilience learning in schools is the ability to embed learning activities in school programs that are linked to relevant curriculums. The introduction of Disaster Preparedness School (DPS) hoped students were able to identify disaster resilience learning and face the disaster occurring. In 2009, the government started developing a pilot project by combining the curriculum disaster education to the curriculum of Disaster Preparedness School (DPS). The purpose of this study was to analyze the cause of inhibition and make a strategy to solve the problem. This study used a literature review approach and source of data search from the literature that obtains via the internet in the form of results of an online library of local, national, and international, and also from books and related regulations. The results of this study are: a) The cause of inhibitions included four indicators like program target inexact, program of socialization less strength, program goal less power, monitoring program less document incomplete; b) The strategy to the development program of DPS would be successful under following conditions: 1) insertion curriculum of disaster mitigation education into several subjects, and into extracurricular activities that exist in schools. 2) conducting DPS Program by proper training that has been done by the ways: right participant, the subject that relates to a local disaster, functional modules, good time setting, monitoring equipment, done routinely and systematically, and also involving the whole stakeholder.